2018
DOI: 10.18355/xl.2018.11.02.33
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism and manipulation: from social philosophy to social psychology

Abstract: The paper deals with the challenges that the modern society development faces in social interaction both at the macro level (international interaction, interaction within individual states) and the micro level (the level of interaction in and between small social groups, and interpersonal communication). Social and philosophical understanding of the phenomena of Machiavellianism and manipulative behavior is a relevant issue because in any of the manifestations they are considered as social constructs developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They are among those who give orders and are motivated only based on personal gain. Ibragimov et al (2018) found that the characteristics of Machiavellianism and manipulation (indirect, hidden and implicit influence, deception, disrespect for moral and ethical norms and social and cultural values, focus on domination, control, coercion, use of force, use of others as objects, objects, programming of ideas, intentions, etc.) are rather features of public administration.…”
mentioning
confidence: 99%
“…They are among those who give orders and are motivated only based on personal gain. Ibragimov et al (2018) found that the characteristics of Machiavellianism and manipulation (indirect, hidden and implicit influence, deception, disrespect for moral and ethical norms and social and cultural values, focus on domination, control, coercion, use of force, use of others as objects, objects, programming of ideas, intentions, etc.) are rather features of public administration.…”
mentioning
confidence: 99%